Waste Management Challenges in Yogyakarta: A Study Using Multiple Perspective Analysis - Putri Rezky, Aulia; Al Khalidi, Said Muhammad; Firdaus, Alfareza; Saputri, Ayu (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2025)
The difficulty of handling waste in Indonesia can be found in big cities such as Yogyakarta. Thus, there is an urgent problem in waste handling and management. This research aims to explore the dynamics of waste problems in Yogyakarta Province as well as alternative solutions using Multiple Perspective Analysis. The method used is qualitative, using secondary data sources and literature studies. The results found are the waste problem in Yogyakarta caused by many factors ranging from conflicts between policy implementers, poor synchronization between governments, lack of budget, technology, adequate facilities, and public awareness to be responsible for the waste produced. Additionally, Yogyakarta local government has not been able to take firm action against companies that produce products with plastic materials that are difficult to decompose. Therefore, implications of this study for a sustainable waste management system that requires effective leadership from the government, efficient infrastructure, and coordination between multi-stakeholders.